Performance analysis of a smaller-capacity straight-bladed VAWT with prospective airfoils - Islam, Mazharul; Amin, M. Ruhul; Ting, David; Fartaj, Amir (American Institute of Aeronautics and Astronautics (AIAA), 2008)
Modern wind turbines are categorized as horizontal axis wind turbines (HAWTs) and vertical axis wind turbines (VAWTs), which are currently being utilized for diversified applications. The basic theoretical advantages of VAWTs are: (i) they accept the wind from any direction, and (ii) the generator, gearbox etc. can be placed on the ground. Selection of airfoil is one of the most critical factor in achieving optimum aerodynamic performance and in determining the optimum dimensions of a fixed-pitch straight-bladed vertical axis wind turbine (SB-VAWT). Airfoil related design changes also have the potential for increasing the cost effectiveness of VAWTs. Most of the earlier research works carried out by different research organizations mainly used NACA symmetric airfoils which were unable to self-start properly. In this paper, detail systematic investigative analyses have been performed with high-lift asymmetric airfoils appropriate for self-starting and better performance of smaller capacity SB-VAWT. In order to do the performance analysis, a computational scheme has been developed using the Cascade Model and XFOIL, a sub-sonic airfoil design and analysis tool developed in MIT. It has been found out that the results obtained from the computational scheme conform reasonably well with the experimental results. Subsequently, three prospective airfoils have been identified using this computational scheme. It has been found that their performance is better than conventionally used NACA 0015 at low tip speed ratio range where the problem of self-starting happens.